Death as surrender - González Faus, José Ignacio (Razón y fe, 2022)
The article attempts to collect opinions of non-believers, with the suspicion that everything may not end with death. It contrasts the current optimistic view of the body as “expression” of the soul with the classical Greek view of the body as “prison” of the soul, looking for the validity of each. And, beyond philosophies on the immortal soul, he analyses a little the Christian hope founded on the resurrection of Jesus and the hope, more glimpsed than founded, that springs from the sparks of eternity that life offers, and that allow us to see death more as an arrival than as a departure. He draws some practical consequences from this and suggests that when something is truly given without being taken from us, it is never lost. Hence the importance of a preparation for death, in the act of consciously accepting it.
Keywords: glimpses; suspicions; trust; body; life as conscious pregnancy; meaning